The Influence of Learning Management System (LMS)-Based Training and Career Development on Employee Competence at PT. Perkebunan Nusantara IV Regional II Medan - Iqbal, Muhammad; Iskandarini, Iskandarini; Rahmadhani, Vivi Gusrini (Program Pascasarjana UIN Sumatera Utara, 2025)
This study examines the influence of Learning Management System (LMS)-based training and career development on employee competence at PT. Perkebunan Nusantara IV Regional II Medan. The research addresses the ongoing challenge of improving employee competence despite the implementation of LMS and career development programs. A quantitative research design was used, and data were collected through structured questionnaires distributed to 123 employees. Multiple linear regression analysis was applied to examine the relationships among variables. The findings reveal that LMS-based training has a significant and dominant effect on employee competence, with greater impact than career development programs. The LMS provides flexibility and accessibility that enhance learning engagement, yet limitations remain, such as the lack of contextual content and alignment with job-specific needs. Career development programs also positively affect competence but show uneven access across employee groups, limiting their full impact. The study concludes that a structured, integrated approach combining LMS training with equitable career development pathways is essential to maximize employee competence. The research highlights the need for organizations to align LMS content with workplace requirements and develop inclusive career strategies. These findings contribute to the human resource development field by offering practical insights for enhancing digital learning systems and career growth in the plantation sector.